Identyfikacja problemów w infobrokerstwie systemowym - Boruszewski, Jarosław (My University, 2014)
The purpose of this article is to provide adequate characteristics of problem identification in systemic information brokerage. A systemic information broker is an interdisciplinary professional who is responsible for creating pertinent content in an organization and who respects the accepted standards of record keeping. According to John Dewey’s theory of inquiry, problem identification is a stage between a felt difficulty and the formulation of the problem. The author of this article proposes a twolevel description of problem identification. At the macro level, problem identification is understood as identifying the respected way of thinking in an organization and, more specifically, as identifying the divergence between the respected way of thinking and one’s declared way of thinking. At the micro level, problem identification involves identifying keywords. Once identified, keywords are used to formulate problems in the form of how-questions.
Keywords: infobrokerstwo; infobrokerstwo systemowe; słowa kluczowe; inquiry; how-questions; information brokerage; identyfikacja problemów; keywords